2021
DOI: 10.3390/ijms22042181
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of OsAAP3 Influences Rice Lesion Mimic and Leaf Senescence by Regulating Arginine Transport and Nitric Oxide Pathway

Abstract: Persistent lesion mimic can cause leaf senescence, affecting grain yield in crops. However, knowledge about the regulation of lesion mimic and leaf senescence in crop plants is still limited. Here, we report that the amino acid transporter OsAAP3, a negative regulator of tiller bud elongation and rice grain yield, is involved in lesion mimic and leaf senescence. Altered expression of OsAAP3 can initiate the nitric oxide signaling pathway through excessive accumulation of arginine in rice leaves, influencing RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…It was shown in Arabidopsis that the AAP8 (Amino Acid Permease 8) plays a key role in amino acid phloem loading and its function strongly affects sink size and number [ 122 ]. Interestingly, a recent paper shows that increasing the expression of the rice OsAAP3 that facilitates the transport of arginine and lysine into the mesophyll cells influences leaf senescence [ 123 ]. The overexpression of OsAAP3 decreases grain yield and leads to lesion mimic and leaf senescence in rice flag leaves by an increase of nitric oxide.…”
Section: Leaf Senescence and Nitrogen Metabolismmentioning
confidence: 99%
“…It was shown in Arabidopsis that the AAP8 (Amino Acid Permease 8) plays a key role in amino acid phloem loading and its function strongly affects sink size and number [ 122 ]. Interestingly, a recent paper shows that increasing the expression of the rice OsAAP3 that facilitates the transport of arginine and lysine into the mesophyll cells influences leaf senescence [ 123 ]. The overexpression of OsAAP3 decreases grain yield and leads to lesion mimic and leaf senescence in rice flag leaves by an increase of nitric oxide.…”
Section: Leaf Senescence and Nitrogen Metabolismmentioning
confidence: 99%
“…In this study, the addition of high concentrations of Lys and Arg inhibited the elongation of first and second axillary buds in rice ( Figure 1 ). One possible explanation is that Lys and Arg can influence antioxidant enzymes activities and photosynthetic pathway by initiating the ROS accumulation and nitric oxide signaling pathway ( Wei et al, 2021 ). Our results also showed that nitrogen metabolism, stress, and photosynthetic pathways play important roles in response to amino acids Lys and Arg in axillary buds.…”
Section: Discussionmentioning
confidence: 99%
“…In poplar (Populus trichocarpa), the Gln content of senescing leaves dramatically increased, and a cationic amino acid transporter, Pt-CAT11, played an important role in the transfer of Gln during the senescence process (Couturier et al, 2010). In rice, overexpression lines of OsAAP3 exhibited accelerated leaf yellowing phenotype, whereas RNA interference (RNAi) lines of OsAAP3 exhibited delayed leaf yellowing (Wei et al, 2021).…”
Section: Amino Acid Metabolism During N Deficiency-induced N Remobili...mentioning
confidence: 99%